Hillforts : Britain, Ireland and the nearer continent : papers from the Atlas of Hillforts of Britain and Ireland Conference, June 2017, edited by Gary Lock and Ian Ralston (Archaeopress archaeology., 2019)
Funded by the AHRC, the Atlas of Hillforts of Britain and Ireland project (2012-2016) involved a team drawn from the Universities of Oxford, Edinburgh and Cork which was responsible for compiling a massive database, now freely available online at https://hillforts.arch.ox.ac, on hillforts in Britain and Ireland. This was underpinned by a major desk-based re-assessment of accessible records. These twelve studies, presented at the end of that exercise to a conference in Edinburgh, and contributed by team members and colleagues, outline the background to and development of the project (Gary Lock) and offer a preliminary assessment of the online digital Atlas (John Pouncett) as well as presenting initial research studies using Atlas data. The volume is profusely illustrated with over 140 figures, including many new maps. Ian Ralston provides a historical assessment of key stages in the enumeration and mapping of these important monuments on both sides of the Irish Sea. The hill- and promontory forts of England, Wales and the Isle of Man are assessed by Ian Brown and those of Ireland by James O'Driscoll, Alan Hawkes and William O'Brien. Stratford Halliday's study of the Scottish evidence focuses on the impact of the application of the Atlas criteria to the records of forts in that country. Simon Maddison deploys Percolation Analysis as an example of the potential re-use of the Atlas data in analysing new distributions; Jessica Murray presents a GIS-based approach to hillfort settings and configurations. Syntheses on insular Early Historic fortified settlements in northern Britain and Ireland, by James O'Driscoll and Gordon Noble, and on hillforts in areas of the nearer Continent are included. The latter comprise an overview by Sophie Krausz on Iron Age fortifications in France and a consideration of the south German records of hillforts and oppida by Axel Posluschny, while Fernando Rodriguez del Cueto tackles the north-western Spanish evidence